A Commentary on “Pain Reduction and Improved Vascular Health Associated with Daily Consumption of an Anti-Inflammatory Dietary Supplement Blend” [Response to Letter] - Hamilton DE; Jensen GS (Journal of Pain Research)
Debby E Hamilton,1 Gitte S Jensen2 1Physician, Holistic Pediatric Consulting, Arvada, CO, 80003, USA; 2NIS Labs, Klamath Falls, OR, 97601, USACorrespondence: Gitte S Jensen, NIS Labs, Esplanade, Klamath Falls, OR, 1437, USA, Tel +1 541 884 0112, Email gitte@nislabs.com